Prevalence of Dental Anomalies and Its Role in Sex Estimation among Children of Jazan Region, Saudi Arabia - Apathsakayan Renugalakshmi; Thilla Sekar Vinothkumar; Ahmed M. Bokhari; Samaher Almahdi; Abdulrahman Almalki; Sudheer Babu Balla; Santosh Kumar Tadakamadla; Zaki Hakami (MDPI AG, 2023)
Background: This study aimed to ascertain the prevalence of dental anomalies and their ability to estimate sex status. Material and Methods: This cross-sectional radiographic study was based on the evaluation of dental anomalies of Saudi children aged between 5 and 17 years. A total of 1940 orthopantomograms (OPG) were screened, of which 1442 were included. All the OPGs were digitally evaluated with ImageJ software. The demographic variables and dental anomaly findings were subjected to descriptive and comparative statistical analysis. Discriminant function analysis was conducted for sex estimation. p value < 0.05 was considered as significant. Results: The mean age of the children in this study was 11.35 ± 0.28 years. At least one dental anomaly was detected in 161 children (11.17%), including 71 males and 90 females. Only 13 children (8.07%) presented with more than one anomaly. The most common dental anomaly detected was root dilaceration (47.83%) followed by hypodontia (31.68%). The least common dental anomaly was infraocclusion (1.86%). The sex prediction accuracy using discriminant function analysis was 62.9% (p < 0.01). Conclusion: The prevalence of dental anomalies was 11.17% with root dilaceration and hypodontia being the most common. The role of dental anomalies in sex estimation was found to be ineffective.